Deposition of titanium dioxide (TiO2) thin films using in-house nano-TiO2 powder - Sahdan, Mohd Zainizan (2012)
The purpose of this study is to fabricate uniform TiO2 thin films using in-house TiO2 nanopowder. The nanopowder was obtained from a tin mining waste (Ilmenite) and its concentration was optimized during fabrication. The TiO2 thin films were characterized by an atomic force microscope (AFM), a surface profiler, an X-ray diffractometer, an Ultra violet- Visible (UV-Vis) and a current-voltage (I-V) measurement system. The relation of the uniformity and the properties of the TiO2 thin films will be discussed in detail in this paper.